Research on Dependable Ionizing Radiation Protection based on Model i* - Tan Hai; Shahnawaz Talpur; Imran Ali Qureshi (Institute of Advanced Engineering and Science, 2013)
The software’s unreliability mostly attributes to an erroneous analysis on the requirements done at the beginning. In this paper, we apply the tool of i* frame requirement modeling and build early requirement model against ionizing radiation. After finding out possible risks and corresponding solutions during the process of modeling analysis, we propose reasoning models against ionizing radiation. The radiation protection system with the above models can figure out the purpose of agents related to radiant source and provide normal service even when the environment software system is being interfered. It can serve the ecological and economical society with stability and development. The model is divided into several sections. Section 1 gives the outline of the dependant software. Section 2 illustrates the i* frame technology. Section 3, 4 and 5 cover the topic of dependant security requirement analysis, SD&SR model on ionizing radiation respectively. Section 6 gives the conclusion. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2020